The Use of Sirah for Hadith Understanding: an Effort to Support Religious Harmony - Ahmad Musyafiq (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
This study aims to formulate the use of Sirah for Hadith understanding, which is broken down into four sub-problems, namely: 1) What are the problems of Hadith understanding; 2) what are the problems of the use of Sirah for Hadith understanding; and 3) how is the application. Data were collected from literature sources, both primary and secondary, which began by the symbolic reading, semantic reading and recording. The analysis carried out during and after data collection, consisting of reduction, classification and display of data. Data analysis was conducted using historical, comparative and hermeneutics methods. The findings of this study are: First, generally the problem of Hadith understanding can be grouped into three categories, namely wurud problems, dalalah problems and comprehensifity problems. The wurud problems associated with efforts to determine hadith maqbul (accepted hadith) and hadith mardud (rejected hadith). The dalalah problems related to an attempt to understand and practice the hadith maqbul. The comprehensifity problems associated with an attempt to obtain data as complete as possible, both from the collections of Hadith and the collection of Sirah. Second, the problem of the use of Sirah for Hadith understanding can be grouped into two categories, namely the problems surrounding the relationship among Sirah, Hadith and Asbab al-Wurud. Based on the comparison among them, it was found that the use of Sirah for Hadith understanding is legitimate and important as the context in addition to Asbab al-Wurud. Third, the application of the use of Sirah for Hadith understanding can be seen through three problems of Hadith understanding above. In wurud problems, the use of Sirah is shown in its position as one of the criterium of matan critics. In dalalah problems, the use of Sirah appears on its position as the socio-historical context that is more extensive than Asbab al-Wurud al-Khashshah and clearer and more valid than Asbab al-Wurud al-‘Ammah. In comprehensifity problem, the use of Sirah looks at his position as a partner for Hadith in providing data. Keywords: Wurud problems, dalalah problems, comprehensifity problems, al-ziyadah, al-takmil and al-tartib